FoxO3 normalizes Smad3-induced arterial smooth muscle cell growth - Francisco, Jake T.; Holt, Andrew W.; Bullock, Michael T.; Williams, Madison D.; Poovey, Cere E.; Holland, Nathan A.; Brault, Jeffrey J.; Tulis, David A. (Frontiers in Physiology, 2023)
Transition of arterial smooth muscle (ASM) from a quiescent, contractile state to a growth-promoting state is a hallmark of cardiovascular disease (CVD), a leading cause of death and disability in the United States and worldwide. While many individual signals have been identified as important mechanisms in this phenotypic conversion, the combined impact of the transcription factors Smad3 and FoxO3 in ASM growth is not known. The purpose of this study was to determine that a coordinated, phosphorylation-specific relationship exists between Smad3 and FoxO3 in the control of ASM cell growth. Using a rat in vivo arterial injury model and rat primary ASM cell lysates and fractions, validated low and high serum in vitro models of respective quiescent and growth states, and adenoviral (Ad-) gene delivery for overexpression (OE) of individual and combined Smad3 and/or FoxO3, we hypothesized that FoxO3 can moderate Smad3-induced ASM cell growth. Key findings revealed unique cellular distribution of Smad3 and FoxO3 under growth conditions, with induction of both nuclear and cytosolic Smad3 yet primarily cytosolic FoxO3; Ad-Smad3 OE leading to cytosolic and nuclear expression of phosphorylated and total Smad3, with almost complete reversal of each with Ad-FoxO3 co-infection in quiescent and growth conditions; Ad-FoxO3 OE leading to enhanced cytosolic expression of phosphorylated and total FoxO3, both reduced with Ad-Smad3 co-infection in quiescent and growth conditions; Ad-FoxO3 inducing expression and activity of the ubiquitin ligase MuRF-1, which was reversed with concomitant Ad-Smad3 OE; and combined Smad3/FoxO3 OE reversing both the pro-growth impact of singular Smad3 and the cytostatic impact of singular FoxO3. A primary takeaway from these observations is the capacity of FoxO3 to reverse growth-promoting effects of Smad3 in ASM cells. Additional findings lend support for reciprocal antagonism of Smad3 on FoxO3-induced cytostasis, and these effects are dependent upon discrete phosphorylation states and cellular localization and involve MuRF-1 in the control of ASM cell growth. Lastly, results showing capacity of FoxO3 to normalize Smad3-induced ASM cell growth largely support our hypothesis, and overall findings provide evidence for utility of Smad3 and/or FoxO3 as potential therapeutic targets against abnormal ASM growth in the context of CVD.